Re-Imagining the Teaching of European History : Promoting Civic Education and Historical Consciousness. - Gómez Carrasco, Cosme Jesús. (Milton : Taylor & Francis Group, 2022)
This book explores the challenges of teaching European history in the 21st century and provides research-informed approaches to history teaching that combine civic education, historical consciousness and the teaching of controversial social issues.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books